A Ghost Trapped: Realization of the 1‐Titanacyclobuta‐2, 3‐diene as the First Four‐Membered Group 4 Metallacycloallene. Issue 30 (7th August 2019) - Rosenthal, U.
Abstract : Very recently the synthesis of the firstfour‐ membered metallacycloallene of a group 4 metal, the very unusual 1‐titanacyclobuta‐2, 3‐diene [ rac ‐(ebthi)Ti[‐C(SiMe3 )=C=C(SiMe3 )‐] ( rac ‐ebthi = rac ‐1, 2‐ethylene‐1, 1′‐bis(η 5 ‐tetrahydroindenyl)) was reported by Reiß and Beweries. This complex has its own story since 2004 when thefive‐ membered metallacycloallene was proposed, for which later many examples were described. Over the years several studies have described preparative and computational attempts to stabilize and describe such a complex, before the successful synthesis of the above mentioned smallerfour‐ membered metallacycloallene. Only by appropriate variation of the cyclopentadienyl ligand of the titanocene complex it was possible now to realize this highly strained compound. Abstract : It's a Long Way toTi ···: Not toTi pperary as in the well‐known song, but toTi tanium. This review accesses the firstfour ‐membered metallacycloallene based on a group 4 metal, the highly unusual ring strained 1‐titanacyclobuta‐2, 3‐diene [ rac ‐(ebthi)Ti[‐C(SiMe3 )=C=C(SiMe3 )‐]. After thefive ‐membered metallacyclocumulene (i ) and thefive‐ membered metallacycloallene (ii ) the smallerfour ‐membered metallacycloallene (iii ) was now realized.